Prostaglandin E2-Induced Immune Suppression via Cytotoxic T-Lymphocyte Antigen 4 in Paratuberculosis - Sajiki, Yamato; Konnai, Satoru; Watari, Kei; Okagawa, Tomohiro; Tanaka, Akina; Kawaji, Satoko; Nagata, Reiko; Maekawa, Naoya; Suzuki, Yasuhiko; Kato, Yukinari; Murata, Shiro; Mori, Yasuyuki; et al. (Infection and immunity, 2022)
Paratuberculosis is a chronic enteritis of ruminants caused by the facultative intracellular pathogen Mycobacterium avium subsp. paratuberculosis. The Th1 response inhibits the proliferation of M. avium subsp. paratuberculosis during the early subclinical stage. However, we have previously shown that immune inhibitory molecules, such as prostaglandin E2 (PGE2), suppress M. avium subsp. paratuberculosis-specific Th1 responses as the disease progresses. To date, the mechanism underlying immunosuppression during M. avium subsp. paratuberculosis infection has not been elucidated. Therefore, in the present study, we investigated the function of cytotoxic T-lymphocyte antigen 4 (CTLA-4) expressed by peripheral blood mononuclear cells (PBMCs) from cattle with paratuberculosis because CTLA-4 expression is known to be elevated in T cells under an M. avium subsp. paratuberculosis experimental infection. M. avium subsp. paratuberculosis antigen induced CTLA-4 expression in T cells from cattle experimentally infected with M. avium subsp. paratuberculosis. Interestingly, both PGE2 and an E prostanoid 4 agonist also induced CTLA-4 expression in T cells. In addition, a functional assay with a bovine CTLA-4-immunogobulin fusion protein (CTLA-4-Ig) indicated that CTLA-4 inhibited gamma interferon (IFN-γ) production in M. avium subsp. paratuberculosis-stimulated PBMCs, while blockade by anti-bovine CTLA-4 monoclonal antibody increased the secretion of IFN-γ and tumor necrosis factor alpha production in these PBMCs. These preliminary findings show that PGE2 has immunosuppressive effects via CTLA-4 to M. avium subsp. paratuberculosis. Therefore, it is necessary to clarify in the future whether CTLA-4-mediated immunosuppression facilitates disease progression of paratuberculosis in cattle.